2015
DOI: 10.1007/s11745-015-4091-z
|View full text |Cite
|
Sign up to set email alerts
|

Low n‐6/n‐3 PUFA Ratio Improves Lipid Metabolism, Inflammation, Oxidative Stress and Endothelial Function in Rats Using Plant Oils as n‐3 Fatty Acid Source

Abstract: Lipid metabolism, inflammation, oxidative stress and endothelial function play important roles in the pathogenesis of cardiovascular disease (CVD), which may be affected by an imbalance in the n-6/n-3 polyunsaturated fatty acid (PUFA) ratio. This study aimed to investigate the effects of the n-6/n-3 PUFA ratio on these cardiovascular risk factors in rats fed a high-fat diet using plant oils as the main n-3 PUFA source. The 1:1 and 5:1 ratio groups had significantly decreased serum levels of total cholesterol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 58 publications
5
80
0
4
Order By: Relevance
“…No studies nity processes. It has been recently demonstrated that high seric levels in n-6/n-3 PUFA ratio induce health benefits while lower ratios might develop adverse effects [42]. In this sense obtained data might reflect possible exercise-induced adverse conditions in sportsmen.…”
Section: Discussionmentioning
confidence: 94%
“…No studies nity processes. It has been recently demonstrated that high seric levels in n-6/n-3 PUFA ratio induce health benefits while lower ratios might develop adverse effects [42]. In this sense obtained data might reflect possible exercise-induced adverse conditions in sportsmen.…”
Section: Discussionmentioning
confidence: 94%
“…For this reason, FAO (2010) [28] recommends ingestion of ω-6 between 2.5-9% and ω3 between 0.5-2%. Appropriate consumption of those fatty acids helps regulating the inflammatory process, oxidative stress and endothelial function [29].…”
Section: Resultsmentioning
confidence: 99%
“…They found that EPA effectively prevented the development and progression of NASH and ameliorated hepatic steatosis in mice [22]. Heerwagen et al revealed that a highfat diet significantly increased the n-3:n-6 PUFA ratio and reduced maternal obesity-associated inflammation in Fat-1 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%